Chronic myelogenous leukemia, a still unsolved problem: pitfalls and new therapeutic possibilities - Flis S; Chojnacki T (Dove Medical Press, 2019)
Sylwia Flis,1 Tomasz Chojnacki2 1Department of Pharmacology, National Medicines Institute, 00-725 Warsaw, Poland; 2Department of Hematology, Military Institute of Medicine, 04-141 Warsaw, Poland Abstract: Chronic myeloid leukemia (CML) is a clonal myeloproliferative disorder of hematopoietic stem cells. At the molecular level, the disorder results from t(9;22)(q34;q11) reciprocal translocation between chromosomes, which leads to the formation of an oncogenic BCR–ABL gene fusion. Instead of progress in the understanding of the molecular etiology of CML and the development of novel therapeutic strategies, clinicians still face many challenges in the effective treatment of patients. In this review, we discuss the pathways of diagnosis and treatment of patients, as well as the problems appearing in the course of disease development. We also briefly refer to several aspects regarding the current knowledge on the molecular basis of CML and new potential therapeutic targets. Keywords: chronic myeloid leukemia, CML, BCR–ABL, tyrosine kinase inhibitors, TKI, TKI withdrawal, stem cells, autophagy